High-efficiency exfoliation of large-area mono-layer graphene oxide with controlled dimension. Issue 1 (December 2017) - Park, Won; Yoon, Yeojoon; Song, Young; Choi, Su; Kim, Seungdu; Do, Youngjin; Lee, Junghyun; Park, Hyesung; Yoon, Dae; Yang, Woo
Abstract In this work, we introduce a novel and facile method of exfoliating large-area, single-layer graphene oxide using a shearing stress. The shearing stress reactor consists of two concentric cylinders, where the inner cylinder rotates at controlled speed while the outer cylinder is kept stationary. We found that the formation of Taylor vortex flow with shearing stress can effectively exfoliate the graphite oxide, resulting in large-area single- or few-layer graphene oxide (GO) platelets with high yields (>90%) within 60 min of reaction time. Moreover, the lateral size of exfoliated GO sheets was readily tunable by simply controlling the rotational speed of the reactor and reaction time. Our approach for high-efficiency exfoliation of GO with controlled dimension may find its utility in numerous industrial applications including energy storage, conducting composite, electronic device, and supporting frameworks of catalyst.